ANALISIS PENGARUH PAJAK HOTEL DAN RESTORAN TERHADAP PENDAPATAN ASLI DAERAH (PAD) - Asep Mulyana; Risma Budianingsih (Jurnal Akuntansi Bisnis dan Ekonomi, 2019)
Locally-generated revanue is the revenue from local taxes, separated regional wealth management and other income. Hotels and restaurants are potential sectors in increasing the effectiveness of hotel and restaurant tax revenues and the contributions provided by hotels and restaurants can spur the economic development of Bandung. The purpose of this study to determine the effect of hotel and restaurant tax on PAD Bandung. The research was conducted at Bandung Revenue Department. The method of analysis used is qualitative research method with descriptive mass formulation approach that is analyzing data of influence of hotel and restaurant tax of year 2011-2016. The data used in this research is secondary data. The statistical test used in this research is doubled linear regression method, and hypothesis test. The results showed that there is influence from hotel tax and restaurant tax to PAD in the year 2011-2016 amounted to 47,511.